Predictors of response to intravenous immunoglobulin in patients with dermatomyositis: the ProDERM study - Charles-Schoeman, Christina; Schessl, Joachim; Bata-Csörgő, Zsuzsanna; Dimachkie, Mazen M; Griger, Zoltan; Moiseev, Sergey; Oddis, Chester V; Schiopu, Elena; Vencovský, Jiri; Clodi, Elisabeth; Levine, Todd; Aggarwal, Rohit (Rheumatology (Oxford, England), 2025)
OBJECTIVES: The phase 3 ProDERM study demonstrated intravenous immunoglobulin (IVIg) was safe and effective in patients with dermatomyositis (DM). This analysis assessed clinical and serological predictors of IVIg response in DM patients from ProDERM. METHODS: ProDERM was a prospective, randomized, placebo-controlled study of DM patients. For weeks 0-16, patients received 2.0 g/kg IVIg (Octagam, 10%) or placebo every 4 weeks. Eligible patients entered the open-label extension phase, where all received IVIg to week 40. Univariate and multivariate analyses examined associations between baseline variables and total improvement score (TIS), including myositis disease activity assessment tool (MDAAT; assessing different organ involvement), and myositis-specific and myositis-associated autoantibodies. RESULTS: Ninety-five patients were enrolled. Univariate analyses found no significant association between TIS at week 16 or 40 and age; sex; ethnicity; disease duration/activity; cutaneous, skeletal, gastrointestinal or muscle disease activity; or previous failed or concomitant medications. Multivariate analysis found patients with higher MDAAT cutaneous scores had a better chance of at least minimal TIS improvement. Higher MDAAT pulmonary scores were associated with a lower, but still considerable, chance of improvement. Patients with TIF1-γ antibodies had a better TIS response; however, after controlling for cutaneous disease activity, there was no significant association between antibody classification (including anti-TIF1-γ) and efficacy outcome. CONCLUSION: IVIg was effective in treating DM patients regardless of demographic features and autoantibody status (for most autoantibodies). Patients with higher cutaneous disease activity and/or anti-TIF1-γ responded best to IVIg, while pulmonary disease activity predicted a lower, but still effective, IVIg response, warranting further investigation. TRIAL REGISTRATION: ClinicalTrials.gov, http://clinicaltrials.gov, NCT02728752.
Keywords: myositis-specific antibodies; Autoantibodies; intravenous immunoglobulin; Humans; dermatomyozitida; anti-TIF1-γ; lidé středního věku; Double-Blind Method; Immunoglobulins, Intravenous; Female; Aged; dospělí; výsledek terapie; senioři; lidé; dvojitá slepá metoda; Dermatomyositis; myositis-associated antibodies; cutaneous; Adult; imunologické faktory; ženské pohlaví; stupeň závažnosti nemoci; Male; autoprotilátky; Middle Aged; autoimmune; Treatment Outcome; Immunologic Factors; Severity of Illness Index; intravenózní imunoglobuliny; mužské pohlaví; prospektivní studie; autoantibody; dermatomyositis; Prospective Studies